TUDUHAN NEPOTISME TERHADAP UTSMAN BIN AFFAN DAN PENGARUHNYA TERHADAP KEKHALIFAHAN ALI BIN ABI THALIB - Murtiningsih Murtiningsih (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2018)
One of the important issues in the leadership of Uthman ibn Affan's caliphate is the nepotism issue. This is due to the vile slander waged by the hypocrites that led to the rebellion and the murder of Uthman ibn Affan tragically. The case had an impact on the caliphate of Ali bin Abi Talib with the emergence of rebellion in Jamal War, the Shiffin War, and the Khawarij who undermined the leadership of the Caliph Ali. The purpose of this study is to determine the validity of the allegations of nepotism addressed to the Caliph Uthman ibn Affan, for remembering that the caliph is the first ten people who converted to Islam and secured into heaven. Historical data proves that the nepotism committed by Uthman ibn Affan did not violate Islamic norms as alleged to him. In addition, the face of nepotism in Indonesia needs to receive great attention, given that nepotism is a disease rooted in the environment of officials to the general public. It is suggested to the government that efforts to eradicate nepotism can be done by introducing a national integrity system and building a clean and healthy political will.